Relations between perception of justice, organizational support, defense of the image and intention of rotation - Cappellozza, Alexandre (2021)
Organizations are impacted by employees who do not get caught up in them and seek better working conditions, policies, fairer practices and support. It verified the perceptions of professionals regarding distributive justice and how the procedures influence the perception organizational’s support, the intention to leave and dissemination of the organizational image. Quantitative research was carried out with 300 workers with analysis of structural equations, five hypotheses of the research model were tested. It was confirmed that Distributive Justice and Procedural Justice influence the Perception of Organizational Support. Organizational Support negatively influences the Rotation Intention, interfering positively in the Organizational Image.